THE APPLICATION OF COOPERATIVE PRINCIPLE IN CHARACTER UTTERANCES IN THE NOVEL TANAH SURGA MERAH BY ARAFAT NUR - Ningtiyas, Siska Tri Cahya; Rijadi, Arief; Pornomo, Bambang Edi (Universitas Negeri Makassar, 2025)
This study aims to describe the form of compliance and violation of cooperative principle by Grice in character utteranaces in the novel Tanah Surga Merah by Arafat Nur, and its use in pragmatic lectures. The method used is descriptive qualitative with documentation techniques and data analysis of the Miles & Huberman model. The collection step began with an intensive reading of the novel Tanah Surga Merah, followed by the identification of data in the form of speech segments and speech contexts that contained elements of the application of the cooperataive principle. The results of the study showed that there was compliance and violation of one to four maxims in various combinations. Compliance reflects the existence of effective and cooperative communication, while violations trigger conflict. These findings are relevant as discussion materials to train students' understanding and critical thinking in pragmatic lectures.